Recognizing religion in democratization processes in Sub-Saharan Africa: a case from niger - Sounaye, Abdoulaye (Ciência & Trópico, 2013)
ABSTRACT This paper examines the development of public Islam in Niger and its transformative effect on the society. Focusing on the emergence of an Islamic civil society and its interventions in the sector of Islamic learning, the paper shows how through Islam, religion and religiosity have become key players in the historical shifts that we observe in contemporary Nigerien urban society. Benefiting from a political reform context, Muslims initiate have introduce institutional changes and practices that further demonstrate the major role of religion in the emerging sociopolitical processes and dynamics. As a value system, a worldview and powerful ideological tool for the socialization of youth, Islam is used to promote a particular identity and citizenship. It is argued that unless we recognize this preeminent role of religion in current sociopolitical processes, we will fail to understand contemporary social dynamics not only in Niger or in the Muslim world, but also across the Global South. KEYWORDS: Niger. Islam. Religion. Sociopolitical processes. RESUMO Este trabalho examina o desenvolvimento de políticas públicas do Islã na Nigéria e seu efeito transformador na sociedade. Centrando-se no surgimento de uma sociedade islâmica civil e as suas intervenções no setor da aprendizagem islâmica, o artigo mostra como, através do Islã, a religião e a religiosidade se tornaram jogadores-chave nas mudanças históricas que observamos na sociedade urbana contemporânea da Nigéria. Beneficiando de um contexto de reforma política, a iniciação dos muçulmanos tem introduzido mudanças institucionais e práticas que ainda demonstram o importante papel da religião nos processos sociopolíticos emergentes e dinâmicos. Como um sistema de valores, visão de mundo e uma ferramenta poderosa ideológica para a socialização da juventude, o Islã é utilizado para promover uma identidade e cidadania particulares. Argumenta-se que se não reconhecermos este papel proeminente da religião nos atuais processos sócio-políticos, vamos deixar de compreender a dinâmica social contemporânea não apenas na Nigéria ou no mundo muçulmano, mas também em todo o Sul Global. PALAVRAS-CHAVE: Nigéria. Islã. Religião. Processos sociopolíticos.